Pulsed ultrasound-stimulated microbubbles alter the tumor blood supply to enhance the efficacy of high-intensity focused ultrasound ablation of vascular tumors - Luo, Dong; Yang, Min; Guo, Jiajun; Hu, Ying; Liu, Le; Ren, Yi; Chen, Wenzhi (Frontiers in Oncology, 2026)
ObjectiveTo investigate the therapeutic effect and mechanism of Pulsed ultrasound stimulated microbubbles to form thrombus and enhance the effect of high-intensity focused ultrasound (HIFU) for ablation of vascular tumors.MethodsAfter EOMA cells were inoculated subcutaneously in mice to form a hemangioendothelioma model, the mice were treated with HIFU alone, pulsed ultrasound combined with microbubbles therapy(PUCM) and the combination of the two methods(PUCM+HIFU) by Contrast ultrasound imaging, HE staining, CD31 immunofluorescence staining to detect the successful establishment of the model and the therapeutic effect. The effect of different treatment groups on apoptosis was detected by TUNEL staining. qRT-PCR, ELISA, CD31 and VEGF immunofluorescence staining were used to detect the changes of cytokines related to thrombosis and angiogenesis. The safety of the treatment was verified through HE staining of important organs and blood biochemical tests.ResultsWe successfully established hemangioendothelioma model, and the characteristics of CEUS are consistent with clinical findings. Pulsed ultrasonic stimulation of microbubbles can form thrombus. Further, PUCM+HIFU exhibits safety and significantly higher ablation effect and promotes apoptosis and necrosis of tumor cells. In addition, PUCM+HIFU can effectively lower the secretion of cytokines related to angiogenesis.ConclusionIn this study, a new therapeutic approach for vascular tumors was proposed, pulsed ultrasound stimulated microbubbles to form thrombus in vascular tumors and then combined with high-intensity focused ultrasound to treat vascular tumors. The combined therapy can better ablate vascular tumors and reduce the formation of blood vessels in the tumors. It is expected to provide a new scheme for the clinical treatment of vascular tumors.